The Role of the International Community and the Responsibility of States to the Existence of Stateless Nations from a Human Rights Perspective - Rajab Ahirullah (Journal of Public Representative and Society Provision, 2026)
UNHCR estimates that 10 million people live without citizenship throughout the world. This condition of statelessness arises from various factors, which nowadays are mostly caused by state succession and prolonged conflicts between countries. The Kurds, Assamese, Palestinians and Ukrainians are some of the cases of statelessness that have received international attention. Therefore, this research was conducted to explore and analyze the development of international human rights law and the role of nation states in overcoming the phenomenon of nations without states. This research is normative juridical research based on secondary data obtained from authoritative and textual materials. The research results show that the escalation of stateless nations is increasing and living in various forms of human rights violations. Various international documents have guaranteed protection for stateless people. However, only a few countries have ratified and adopted international agreements, while their implementation only reaches the level of international commitment. In fact, systematic neglect and discrimination still occurs. There is different treatment between adopting countries and countries that do not adopt international conventions in viewing stateless people. Indonesia, Japan and the Middle East apply various criteria that serve to hinder the acceptance of stateless persons. Meanwhile, the Philippines is building a system that allows the fulfillment and protection of the rights of stateless people. Therefore, there needs to be international collaboration in building global, regional and domestic systems and networks that enable the facilitation of stateless people at a better level regardless of national origin, religion, race and other identities.